Precalculus (10th Edition)

Published by Pearson
ISBN 10: 0-32197-907-9
ISBN 13: 978-0-32197-907-0

Chapter 5 - Exponential and Logarithmic Functions - 5.3 Exponential Functions - 5.3 Assess Your Understanding - Page 280: 4



Work Step by Step

The general formula for the average rate of change from $x=a$ to $x=b$ is $\frac{f(b)-f(a)}{b-a}.$. Using the formula above gives: $\frac{f(4)-f(0)}{4-0}=\frac{(3\cdot4-5)-(3\cdot 0 -5)}{4}=\frac{7-(-5)}{4}=\frac{7+5}{4}=\frac{12}{4}=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.